Splendid and Seldom Isolated: The Paleobiogeography of Patagonia - Wilf, Peter; Cuneo, Nestor Ruben; Escapa, Ignacio Hernan; Pol, Diego; Woodburne, Michael (Annual Review of Earth and Planetary Sciences)
The idea that South America was an island continent over most of the Cenozoic, during which its unusual mammalian faunas evolved in isolation, is outstandingly influential in biogeography. Although large numbers of recent fossil discoveries and related advances require that the original isolation concept be significantly modified, it is still repeated in much current literature. The persistence of the idea inspired us to present here an integrated paleobiogeographic account of mammals, reptiles, and plants from the Jurassic to the Paleogene of Patagonia, which has by far the richest fossil record on the continent. All three groups show distribution patterns that are broadly consistent with South America's long separation history, first from Laurasia by the Late Jurassic, then from Africa and India-Madagascar during the late Early Cretaceous, and finally from Antarctica and Australia during the early-middle Eocene, after which “isolation” finally commenced. We highlight areas of promising future research and provide an updated view of South American isolation. Fil: Wilf, Peter. University of Pennsylvania; Estados Unidos Fil: Cuneo, Nestor Ruben. Museo Paleontológico Egidio Feruglio; Argentina Fil: Escapa, Ignacio Hernan. Museo Paleontológico Egidio Feruglio; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Pol, Diego. Museo Paleontológico Egidio Feruglio; Argentina Fil: Woodburne, Michael. Museum of Northern Arizona. Department of Geology; Estados Unidos